Molecular markers of VEGF, TNF-α and TNF-β IN bladder cancer patients at stage T3N0M0 and their relationship with the degree of tumor neoplasia - Fedevych, O.; Fedevych, V.; Pasichnyk, S. (Journal of Education, Health and Sport, 2023)
17 bladder cancer patients, stage T3N0M0 (main group), were included in the study. There were 10 men (mean age 58.2 ± 6.2 years) and 7 women (mean age 59.5 ± 2.4 years). Clinical data of 12 healthy individuals were used as a control. According to statistic data, the average level of VEGF in bladder cancer patients urine was 246.55± 6.90 pg/ml which significantly exceeded this indicator in the control group (129.21± 7.60 pg/ml), the difference was statistically significant At bladder cancer diagnosis the sensitivity and specificity of the urinary level of TNF-α was low and amounted to 30% and 20%, respectively, and the level of TNF-β was even lower - 25% and 20%, respectively, which is not representative for the pathology under study.